SCIENTIFIC INTERPRETATION OF THE MEANING OF FORM IN THE TEACHING OF ENGLISH GRAMMAR - Kurbanova, Muxabbat (Журнал иностранных языков и лингвистики, 2023)
The basis of our article is that forms-based teaching has a solid foundation in language teaching, while the argument is whether forms-based teaching is specific or implicit. Meanwhile, based on the achievements and methods of mastering the first language, foreign language learners begin to learn to master a foreign language in a natural environment. First, it shows that students with form-based learning are faster and better at learning speed and proficiency, suggesting that form-based learning supports language acquisition.